Honey-baited FTA cards in box gravid traps for the assessment of Usutu virus circulation in mosquito populations in Germany - Fynmore, Noelle; Lühken, Renke; Kliemke, Konstantin; Lange, Unchana; Schmidt-Chanasit, Jonas; Lurz, Peter W. W.; Becker, Norbert (Acta tropica, 2022)
Usutu virus (USUV) is becoming increasingly important to veterinary and human health in Germany. USUV has been implicated in mass die-off events of birds, especially of blackbirds (Turdus merula), and has experienced significant range expansion in the years since its first detection in 2010. Current detection methods rely primarily on dead bird surveillance or mass mosquito collection using CO2 as the main attractant. Dead bird surveillance can result in detection of disease circulation past the point at which control efforts would be most impactful. Vector surveillance offers the opportunity to detect disease circulation before significant outbreaks occur. However, current methods result in collections of extremely large numbers of predominantly nulliparous female mosquitoes who have not yet taken a blood meal. This study sought to test whether box gravid traps could successfully trap USUV infected gravid Culex mosquitoes, and if viral RNA could be successfully transferred and stabilised on an FTA card. During the month of August 2020, 18 Reiter-Cummings style box gravid traps with honey-baited FTA cards were set in a region of known USUV circulation around the southern border of Hesse, Germany. Four 48-hour trapping rounds were conducted. All mosquitoes and FTA cards were collected and stored during transport to the laboratory on dry ice. Samples and FTA cards were then transferred and stored in a freezer at -5 °C until identification. Identification was carried out on a chill plate before being sent with overnight courier in a styrofoam box with cooling elements for virus detection with a modified generic flavivirus RT-PCR. Mosquitoes were separated into pools by trap, date, species and feeding status. 2003 mosquitoes were caught in four rounds of trapping, 1834 or 88% of which were female Culex mosquitoes used for examination. 13 pools of mosquitoes and four FTA cards tested positive for USUV. No positive FTA cards were found in traps with positive mosquitoes and no positive mosquitoes were found in traps with positive FTA cards. Although fewer FTA cards than expected returned a positive result, this may have been a result of the extreme conditions experienced in the field and highlights the need to establish the temperature and humidity boundaries such a collection method can withstand. Box gravid traps however, provided a highly effective and targeted approach for capturing gravid female Culex mosquitoes, the most appropriate subpopulation for testing for USUV. Additionally, the simplicity and effectiveness of this trapping and surveillance method make it an attractive option for use as an early warning system, including for large scale surveillance programmes.